Isolating membrane and preparation method thereof, secondary battery and electric device

CN119137798APending Publication Date: 2024-12-13CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202280095268.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing battery isolation films are easily punctured by lithium dendrites or sodium dendrites, causing short circuits. Poor electrolyte wettability affects the charge and discharge rate, and they easily shrink when heated, posing safety risks.

Method used

A mixed material layer isolation film containing inorganic materials and dispersants is used to delay the puncture phenomenon through the reaction of inorganic materials with lithium dendrites or sodium dendrites, improve electrolyte wettability and heat shrinkage performance, and avoid consuming metal due to reaction with the negative electrode.

Benefits of technology

It extends the battery life, improves the charge and discharge rate and safety, and ensures the first Coulomb efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137798A_ABST
    Figure CN119137798A_ABST
Patent Text Reader

Abstract

The invention provides an isolating membrane, a method for preparing the isolating membrane, a secondary battery and an electric device. The isolating membrane comprises a first base material layer, a mixed material layer and a second base material layer, the mixed material layer is arranged between the first base material layer and the second base material layer; the mixed material layer comprises an inorganic material and a dispersing agent; wherein the electronic conductivity sigma of the isolating membrane is greater than 1 * 10 <-13 > mS / cm and less than 1 * 10 <-1 > mS / cm. The isolating membrane provided by the invention can delay the occurrence of puncturing the diaphragm by lithium dendrites or sodium dendrites, delay the occurrence of short circuit in the battery, prolong the service life of the battery, improve the wettability of the isolating membrane to an electrolyte, improve the charge and discharge rate of the battery, improve the thermal shrinkage performance of the battery, improve the safety of the battery and improve the initial coulombic efficiency of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Separator and preparation method thereof, secondary battery and electric device Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an isolation membrane, a method for preparing the isolation membrane, a secondary battery, and an electrical device. Background Art

[0002] In recent years, with the increasing application of batteries, they have become widely used in energy storage systems such as hydropower, thermal, wind, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. With the rapid development of batteries, higher requirements have been placed on their energy density, cycle performance, and safety performance. Currently, the separators used in batteries are easily punctured by lithium or sodium dendrites on the negative electrode sheet, causing internal short circuits and seriously shortening the battery life. Furthermore, existing separators have poor electrolyte wettability, resulting in low lithium or sodium ion conductivity, which affects the battery's charge and discharge rates. Furthermore, existing separators are prone to severe shrinkage when heated, which can lead to serious safety issues.

[0003] Summary of the Invention

[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a separator, a method for preparing a separator, a secondary battery, and an electrical device. The separator of the present application can delay the occurrence of lithium dendrites or sodium dendrites piercing the separator, thereby delaying the occurrence of short circuits in the battery and extending the battery life; the separator of the present application can improve the wettability of the separator to the electrolyte, increase the transmission rate of sodium ions or lithium ions, and increase the charge and discharge rate of the battery; the separator of the present application can also improve the thermal shrinkage performance of the battery and improve the battery safety; and the separator of the present application can prevent the inorganic material from reacting with the negative electrode to consume lithium or sodium metal, thereby improving the first coulombic efficiency of the battery.

[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides an isolation film, comprising a first substrate layer, a mixed material layer, and a second substrate layer; the mixed material layer is disposed between the first substrate layer and the second substrate layer; the mixed material layer comprises an inorganic material and a dispersant; wherein,

[0006] The electronic conductivity σ of the isolation membrane satisfies: 1×10 -13 mS / cm<σ<1×10 -1 mS / cm.

[0007] Under the action of an electric field, the holes and electrons in the inorganic material move in a directed manner, making the inorganic material electronically conductive; inorganic materials have different crystalline forms in their structure, and different crystalline forms have different effects on electronic conductivity, which causes the same type of inorganic materials to exhibit a wide range of electronic conductivity distribution due to structural differences; when the isolation membrane contains inorganic materials, the electronic conductivity of the isolation membrane also exhibits a wide range of variation.

[0008] Therefore, the present application adopts an isolation membrane that meets a certain electronic conductivity to make the inorganic material in the mixed material layer react with the lithium dendrites or sodium dendrites on the negative electrode sheet, delaying the occurrence of lithium dendrites or sodium dendrites piercing the diaphragm, delaying the occurrence of short circuit in the battery, extending the service life of the battery, and reducing the deposition of lithium ions on the surface of the isolation membrane, thereby reducing the self-discharge and internal short circuit in the battery; the present application improves the wettability of the isolation membrane to the electrolyte through the mixed material layer, improves the transmission rate of sodium ions or lithium ions, and improves the charge and discharge rate of the battery; the present application improves the thermal shrinkage performance of the battery by adopting the mixed material layer, and improves the safety of the battery; and when the negative electrode is lithium metal or sodium metal, the present application separates the mixed material layer and the negative electrode through the first substrate layer or the second substrate layer, avoiding the reaction of the mixed material layer with the negative electrode and consuming lithium or sodium metal in advance, thereby ensuring the first coulombic efficiency of the battery.

[0009] In any embodiment, the inorganic material is selected from one or more of the following (1)-(3):

[0010] (1) Elemental silicon;

[0011] (2) oxides, nitrides and fluorides of one or more elements selected from silicon, aluminum, iron, titanium, cobalt, nickel, manganese, tin, zinc, barium and copper;

[0012] (3) Phosphates of one or more elements selected from aluminum, iron, titanium, cobalt, nickel, manganese, tin, zinc, barium and copper.

[0013] In any embodiment, the inorganic material is one or more selected from silicon dioxide, silicon monoxide, silicon, zinc oxide, tin oxide, copper oxide, iron phosphate, barium titanate, cobalt oxide, manganese oxide, iron oxide, copper nitride and lithium aluminum titanium phosphate.

[0014] The mixed material layer using the above-mentioned inorganic materials can react with lithium dendrites or sodium dendrites, further delaying the occurrence of lithium dendrites or sodium dendrites piercing the isolation membrane, delaying the occurrence time of short circuit in the battery, and extending the service life of the battery; the mixed material layer using the above-mentioned inorganic materials further improves the wettability of the isolation membrane to the electrolyte, improves the transmission rate of sodium ions or lithium ions, and improves the battery charge and discharge rate; the mixed material layer containing the above-mentioned inorganic materials further improves the thermal shrinkage performance of the battery and improves the battery safety.

[0015] In any embodiment, based on the total mass of the mixed material layer, the mass content of the inorganic material is 75%-99.7%, and the mass content of the dispersant is 0.1%-15%, optionally 0.1%-5%.

[0016] The above-mentioned mass content is conducive to promoting the reaction between the mixed material layer and lithium dendrites or sodium dendrites, further delaying the occurrence of lithium dendrites or sodium dendrites piercing the diaphragm, delaying the occurrence of short circuit in the battery caused by this, and extending the service life of the battery. At the same time, it can keep the inorganic material uniformly dispersed in the mixed material layer to ensure the normal function of the mixed material layer.

[0017] In any embodiment, the particle size D of the inorganic material v 50 and the average pore size of the first substrate layer is 1:1-243:1; and / or,

[0018] Particle size D of inorganic materials v The ratio of the average pore size of the pore size 50 to the average pore size of the second substrate layer is 1:1-243:1.

[0019] The above ratio range is conducive to the lithium dendrites or sodium dendrites contacting the inorganic material particles after piercing the substrate layer, and is also conducive to better reaction kinetics between the mixed material layer and the lithium dendrites or sodium dendrites; and the above ratio range reduces the blockage of the pores on the substrate layer by the inorganic material particles.

[0020] In any embodiment, the dispersant is selected from one or more of sodium polyacrylate, ammonium polyacrylate, sodium hexafluorophosphate, sodium carboxymethyl cellulose, hydrolyzed polymaleic anhydride, acrylic acid block polymer, polyester block polymer, polyethylene glycol type polyol, polyvinyl alcohol and polyethyleneimine derivatives.

[0021] This is beneficial to the uniform distribution of inorganic materials in the mixed material layer, helps the mixed material layer to react normally with lithium dendrites or sodium dendrites, delays the lithium dendrites or sodium dendrites from piercing the diaphragm, delays the occurrence of battery short circuit caused by lithium or sodium precipitation, and extends the service life of the battery.

[0022] In any embodiment, the thickness of the mixed material layer is 0.5-10 μm;

[0023] Optionally, the isolation film has a thickness of 11-24 μm.

[0024] The above-mentioned thickness of the mixed material layer and the thickness of the isolation membrane can, on the one hand, ensure that the mixed material layer can react with the lithium dendrites or sodium dendrites on the negative electrode sheet to delay the occurrence of lithium dendrites or sodium dendrites piercing the diaphragm and delay the occurrence of battery short circuit caused by lithium or sodium precipitation. On the other hand, it reduces the volume occupied by the isolation membrane and improves the energy density of the battery cell.

[0025] In any embodiment, the mixed material layer further comprises a polymer, and the polymer is selected from one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB);

[0026] Optionally, based on the total mass of the mixed material layer, the mass content of the polymer is 0.1%-20%.

[0027] The polymer helps the components of the hybrid material layer to adhere to each other.

[0028] In any embodiment, a protective layer is further provided on the surface of the first substrate layer remote from the mixed material layer and / or on the surface of the second substrate layer remote from the mixed material layer. Optionally, the protective layer comprises one or more selected from alumina and boehmite. This can further improve the wettability of the separator to the electrolyte and the high-voltage resistance of the separator.

[0029] The second aspect of the present application also provides a method for preparing an isolation film, comprising the following steps:

[0030] coating a slurry comprising an inorganic material, a dispersant, and optionally a polymer on the first substrate layer to obtain the first substrate layer provided with the mixed material layer;

[0031] Laminating a second substrate layer on the surface of the mixed material layer away from the first substrate layer to obtain a separator;

[0032] The isolation film includes a first substrate layer, a mixed material layer, and a second substrate layer; the mixed material layer is arranged between the first substrate layer and the second substrate layer; the mixed material layer contains an inorganic material, a dispersant, and an optional polymer; the electronic conductivity σ of the isolation film satisfies: 1×10 -13 mS / cm<σ<1×10 -1 mS / cm; the inorganic material, dispersant and polymer are as defined in the first aspect of the present application.

[0033] Therefore, the present application delays the occurrence of lithium dendrites or sodium dendrites piercing the diaphragm by allowing the mixed material layer to react with the lithium dendrites or sodium dendrites on the negative electrode sheet, delays the occurrence of short circuit in the battery, and extends the service life of the battery. In addition, it can reduce the amount of lithium ion deposition on the surface of the isolation membrane, thereby reducing self-discharge and internal short circuit in the battery. The present application improves the wettability of the isolation membrane to the electrolyte through the mixed material layer, increases the transmission rate of sodium ions or lithium ions, and increases the charge and discharge rate of the battery. The present application improves the thermal shrinkage performance of the battery and improves the safety of the battery by adopting the mixed material layer. Moreover, when the negative electrode is lithium metal or sodium metal, the present application separates the mixed material layer from the negative electrode through the first substrate layer or the second substrate layer, avoiding the reaction of the mixed material layer with the negative electrode and consuming lithium or sodium metal in advance, thereby ensuring the first coulombic efficiency of the battery.

[0034] A third aspect of the present application provides a secondary battery, comprising the isolation membrane of the first aspect of the present application or the isolation membrane prepared by the method of the second aspect of the present application.

[0035] In any embodiment, in the battery, the positive electrode active material includes one or more selected from lithium iron phosphate, nickel-cobalt-manganese ternary material, lithium manganate, lithium cobaltate and lithium nickelate; and / or, the negative electrode active material includes one or more selected from graphite, silicon-carbon compounds, silicon oxides and lithium metal.

[0036] A fourth aspect of the present application provides an electrical device comprising the secondary battery according to the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application.

[0038] FIG. 2 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 1 .

[0039] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0040] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application.

[0041] FIG. 5 is an exploded view of the battery pack shown in FIG. 4 according to an embodiment of the present application.

[0042] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0043] Description of reference numerals:

[0044] 1 battery pack; 2 upper case; 3 lower case; 4 battery module; 5 secondary battery; 51 housing; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION

[0045] Below, the embodiments of the isolation membrane and its preparation method, secondary battery, battery module, battery pack and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0046] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0047] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0048] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0049] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.

[0050] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.

[0051] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0052] [Secondary battery]

[0053] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged to activate the active materials after discharge and continue to be used.

[0054] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. During the battery's charge and discharge process, active ions (such as lithium ions and sodium ions) are embedded and released back and forth between the positive and negative electrode sheets. The separator is set between the positive and negative electrode sheets, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte between the positive and negative electrode sheets mainly plays the role of conducting active ions.

[0055] [Isolation film]

[0056] One embodiment of the present application provides a separator, comprising a first substrate layer, a mixed material layer, and a second substrate layer; the mixed material layer is disposed between the first substrate layer and the second substrate layer; the mixed material layer comprises an inorganic material and a dispersant; wherein,

[0057] The electronic conductivity σ of the isolation membrane satisfies: 1×10 -13 mS / cm<σ<1×10 -1 mS / cm; alternatively, 1×10 -11mS / cm<σ<1×10 -3 mS / cm, more preferably, 1.5×10 -11 mS / cm<σ<9×10 -4 mS / cm, for example 10 -10 mS / cm, 10 -9 mS / cm, 10 -8 mS / cm, 10 -6 mS / cm, 10 -5 mS / cm, 10 -4 mS / cm and ranges consisting of any two of the above values ​​as endpoints.

[0058] Under the action of an electric field, the holes and electrons in the inorganic material move in a directed manner, making the inorganic material electronically conductive; inorganic materials have different crystalline forms in their structure, and different crystalline forms have different effects on electronic conductivity, which causes the same type of inorganic materials to exhibit a wide range of electronic conductivity distribution due to structural differences; when the isolation membrane contains inorganic materials, the electronic conductivity of the isolation membrane also exhibits a wide range of variation.

[0059] Although the mechanism is still unclear, the applicant unexpectedly found that: first, the ends of the lithium dendrites or sodium dendrites on the negative electrode sheet pierce the first substrate layer or the second substrate layer and come into contact with the mixed material layer, and the electronic conductivity σ of the separator is greater than 1×10 -13 mS / cm, it is conducive to the reaction between the inorganic material in the mixed material layer and the lithium dendrites or sodium dendrites, thereby delaying the occurrence time of lithium dendrites or sodium dendrites piercing the separator, delaying the occurrence of short circuit in the battery, and extending the service life of the battery; and the electronic conductivity σ of the separator is less than 1×10 -1 mS / cm, which can reduce the amount of lithium ion deposition on the surface of the isolation membrane, thereby reducing the self-discharge and internal short circuit inside the battery; secondly, the mixed material layer of the present application has a strong affinity for the electrolyte, which improves the wettability of the isolation membrane to the electrolyte, increases the transmission rate of sodium ions or lithium ions, and thus increases the charge and discharge rate of the battery; thirdly, the mixed material layer of the present application is not easy to shrink when heated, which improves the thermal shrinkage performance of the battery and improves the safety of the battery; moreover, when the negative electrode is lithium metal or sodium metal, the present application separates the mixed material layer from the negative electrode through the first substrate layer or the second substrate layer, avoiding the reaction between the mixed material layer and the negative electrode and consuming the lithium or sodium metal in advance, thereby ensuring the first coulombic efficiency of the battery.

[0060] In some embodiments, the electronic conductivity σ of the isolation membrane can be measured by conventional methods in the art, for example, by the following specific method:

[0061] Using lithium iron phosphate as the positive electrode, graphite as the negative electrode, and the intermediate layer as the separator to be tested, a thermal pressure resistance meter is used to perform impedance testing under certain pressure and voltage. The test area S of the separator is used to measure the resistance value R of the separator. The electronic conductivity σ of the separator is calculated according to the following formula;

[0062] R=S / (σ×l)

[0063] Wherein, l = H × (1-porosity), H is the initial thickness of the isolation membrane, and l is the thickness of the isolation membrane after the pores are eliminated under the above pressure;

[0064] The above porosity test method:

[0065] The thickness and area of ​​the diaphragm are measured, and the apparent volume V of the diaphragm is calculated. The weight M of the diaphragm is measured, and ρ represents the theoretical density of the substrate in the diaphragm. The porosity P of the diaphragm is calculated according to the following formula.

[0066]

[0067] In some embodiments, the inorganic material is selected from one or more of the following (1)-(3):

[0068] (1) Elemental silicon;

[0069] (2) oxides, nitrides and fluorides of one or more elements selected from silicon, aluminum, iron, titanium, cobalt, nickel, manganese, tin, zinc, barium and copper;

[0070] (3) Phosphates of one or more elements selected from aluminum, iron, titanium, cobalt, nickel, manganese, tin, zinc, barium and copper.

[0071] In some embodiments, the inorganic material is one or more selected from the group consisting of silicon dioxide, silicon monoxide, silicon, zinc oxide, tin oxide, copper oxide, iron phosphate, barium titanate, cobalt oxide, manganese oxide, iron oxide, copper nitride, and lithium aluminum titanium phosphate.

[0072] The mixed material layer using the above-mentioned inorganic materials can react with lithium dendrites or sodium dendrites, further delaying the occurrence of lithium dendrites or sodium dendrites piercing the isolation membrane, delaying the occurrence time of short circuit in the battery, and extending the service life of the battery; the mixed material layer using the above-mentioned inorganic materials further improves the wettability of the isolation membrane to the electrolyte, improves the transmission rate of sodium ions or lithium ions, and improves the battery charge and discharge rate; the mixed material layer containing the above-mentioned inorganic materials further improves the thermal shrinkage performance of the battery and improves the battery safety.

[0073] In some embodiments, based on the total mass of the mixed material layer, the mass content of the inorganic material is 75%-99.7%, for example, 98.5%, 94%, 90%, 85%, 80%, 76%, and the mass content of the dispersant is 0.1%-15%, optionally 0.1%-5%, for example, 0.5%, 1%, 4%, 5%, and a range consisting of any two of the above values ​​as endpoints.

[0074] The above-mentioned mass content is conducive to promoting the reaction between the mixed material layer and lithium dendrites or sodium dendrites, further delaying the occurrence of lithium dendrites or sodium dendrites piercing the diaphragm, delaying the occurrence of short circuit in the battery caused by this, and extending the service life of the battery. At the same time, it can keep the inorganic material uniformly dispersed in the mixed material layer to ensure the normal function of the mixed material layer.

[0075] In some embodiments, the particle size D of the inorganic material is v The ratio of the pore size of the first substrate layer to the average pore size of the first substrate layer is 1:1-243:1, for example, 4:1, 5:1, 8:1, 10:1, 11:1, 12:1, 14:1, 15:1, 16:1, 19:1, 20:1, 27:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 100:1, 120:1, 140:1, 160:1, 180:1, 200:1, 220:1, and ranges consisting of endpoints of any two of the above values; and / or

[0076] Particle size D of inorganic materials v 50 to the average pore size of the second substrate layer is 1:1-243:1, for example 4:1, 5:1, 8:1, 10:1, 11:1, 12:1, 14:1, 15:1, 16:1, 19:1, 20:1, 27:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 100:1, 120:1, 140:1, 160:1, 180:1, 200:1, 220:1 and a range consisting of any two of the above values ​​as endpoints.

[0077] The above ratio range is conducive to the lithium dendrites or sodium dendrites contacting the inorganic material particles after piercing the substrate layer, and is also conducive to better reaction kinetics between the mixed material layer and the lithium dendrites or sodium dendrites; and the above ratio range reduces the blockage of the pores on the substrate layer by the inorganic material particles.

[0078] In some embodiments, the dispersant is selected from one or more of sodium polyacrylate, ammonium polyacrylate, sodium hexafluorophosphate, sodium carboxymethyl cellulose, hydrolyzed polymaleic anhydride, acrylic acid block polymers, polyester block polymers, polyethylene glycol-type polyols, polyvinyl alcohol, and polyethyleneimine derivatives.

[0079] This facilitates the uniform distribution of the inorganic material in the mixed material layer, helps the mixed material layer react normally with lithium dendrites or sodium dendrites, delays the lithium dendrites or sodium dendrites from piercing the separator, delays the occurrence of battery short circuits caused by lithium or sodium precipitation, and extends the battery life. Some of the above-mentioned dispersants are polymers, which meet the molecular weight and distribution requirements of conventional polymer dispersants in the relevant technical field.

[0080] In some embodiments, the thickness of the mixed material layer is 0.5-10 μm, for example 3 μm;

[0081] Optionally, the thickness of the isolation film is 11-24 μm, for example, 14 μm, 15 μm, 17 μm, 19 μm, and a range consisting of any two of the above values ​​as endpoints.

[0082] The above-mentioned thickness of the mixed material layer and the thickness of the isolation membrane can, on the one hand, ensure that the mixed material layer can react with the lithium dendrites or sodium dendrites on the negative electrode sheet to delay the occurrence of lithium dendrites or sodium dendrites piercing the diaphragm and delay the occurrence of battery short circuit caused by lithium or sodium precipitation. On the other hand, it reduces the volume occupied by the isolation membrane and improves the energy density of the battery cell.

[0083] In some embodiments, the mixed material layer further comprises a polymer, and the polymer is selected from one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB);

[0084] Optionally, based on the total mass of the mixed material layer, the mass content of the polymer is 0.1%-20%, for example, 0.2%, 1%, 1.4%, 10% and a range consisting of any two of the above values ​​as endpoints.

[0085] The polymer helps the components in the mixed material layer to adhere to each other. The polymer meets the conventional requirements of the art for molecular weight and distribution of polymers having an adhesive effect. Optionally, the weight average molecular weight of the polymer is 300,000-10,000,000, for example, 500,000.

[0086] In some embodiments, a protective layer is further provided on the surface of the first substrate layer away from the mixed material layer and / or on the surface of the second substrate layer away from the mixed material layer. Optionally, the protective layer comprises one or more selected from alumina and boehmite. This can further improve the separator's wettability to the electrolyte and its high-voltage resistance.

[0087] In some embodiments, the first substrate layer and the second substrate layer comprise a substrate, and the substrate in the first substrate layer and the second substrate layer are independently selected from one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber.

[0088] The use of the above-mentioned substrate is conducive to separating the mixed material layer from the negative electrode, avoiding the reaction between the mixed material layer and the negative electrode to consume lithium or sodium metal in advance, thereby improving the first coulombic efficiency of the battery.

[0089] [Method for preparing separator]

[0090] The present invention provides a method for preparing an isolation film, comprising the following steps:

[0091] coating a slurry comprising an inorganic material, a dispersant, and optionally a polymer on the first substrate layer to obtain the first substrate layer provided with the mixed material layer;

[0092] Laminating a second substrate layer on the surface of the mixed material layer away from the first substrate layer to obtain a separator;

[0093] The isolation film includes a first substrate layer, a mixed material layer, and a second substrate layer; the mixed material layer is arranged between the first substrate layer and the second substrate layer; the mixed material layer contains an inorganic material, a dispersant, and an optional polymer; the electronic conductivity σ of the isolation film satisfies: 1×10 -13 mS / cm<σ<1×10 -1 mS / cm; alternatively, 1×10 -11 mS / cm<σ<1×10 -3 mS / cm, more preferably, 1.5×10 -11 mS / cm<σ<9×10 -4 mS / cm, for example 10 -10 mS / cm, 10 -9 mS / cm, 10 -8 mS / cm, 10 -6 mS / cm, 10 -5 mS / cm, 10 -4 mS / cm and the range consisting of any two of the above values ​​as endpoints; the definitions of inorganic materials, dispersants and polymers are as in [Isolation Film].

[0094] As a result, the ends of the lithium dendrites or sodium dendrites on the negative electrode sheet pierce the first substrate layer or the second substrate layer and contact the mixed material layer, and the electronic conductivity σ of the separator is greater than 1×10 -13mS / cm, it is conducive to the reaction between the mixed material layer and the lithium dendrites or sodium dendrites, thereby delaying the occurrence of lithium dendrites or sodium dendrites piercing the separator, delaying the occurrence of short circuit in the battery, and extending the service life of the battery; and the electronic conductivity σ of the separator is less than 1×10 -1 mS / cm, which can reduce the amount of lithium ion deposition on the surface of the isolation membrane, thereby reducing the self-discharge and internal short circuit inside the battery; the present application improves the wettability of the isolation membrane to the electrolyte through the mixed material layer, increases the transmission rate of sodium ions or lithium ions, and increases the charge and discharge rate of the battery; the use of the mixed material layer improves the thermal shrinkage performance of the battery and improves the safety of the battery; and when the negative electrode is lithium metal or sodium metal, the present application separates the mixed material layer from the negative electrode through the first substrate layer or the second substrate layer, avoiding the reaction between the mixed material layer and the negative electrode and consuming lithium or sodium metal in advance, thereby ensuring the first coulombic efficiency of the battery.

[0095] [Positive electrode]

[0096] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0097] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0098] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0099] In some embodiments, the positive electrode active material may adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0100] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.

[0101] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0102] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0103] [Negative electrode]

[0104] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0105] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0106] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0107] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0108] In some embodiments, the negative electrode film layer may further include a binder. For example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0109] In some embodiments, the negative electrode film layer may further include a conductive agent. For example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0110] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0111] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0112] [Electrolytes]

[0113] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0114] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0115] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0116] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0117] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0118] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0119] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0120] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0121] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 shows a secondary battery 5 having a square structure as an example.

[0122] In some embodiments, referring to FIG2 , the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0123] Secondary batteries come in the form of battery cells, battery modules, and battery packs. In some embodiments, battery cells can be assembled into a battery module, which can contain one or more battery cells. The specific number can be selected by those skilled in the art based on the application and capacity of the battery module.

[0124] FIG3 shows an example battery module 4. Referring to FIG3 , within the battery module 4, multiple battery cells 5 may be arranged sequentially along the length of the battery module 4. Of course, they may also be arranged in any other manner. Furthermore, the multiple battery cells 5 may be secured together using fasteners.

[0125] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.

[0126] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0127] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be placed over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0128] In addition, the present application also provides an electrical device, which includes the secondary battery provided in the present application. The secondary battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device can include, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0129] As an electrical device, a secondary battery can be selected according to its usage requirements.

[0130] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0131] [Example]

[0132] The following examples of the present application are described. The examples described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the examples, the techniques or conditions described in the literature in this area or the product specifications are used. Where the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.

[0133] Example 1

[0134] 1. Preparation of positive electrode sheet:

[0135] The positive electrode active material lithium iron phosphate, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black are dissolved in the solvent N-methylpyrrolidone (NMP) in a mass ratio of 0.9:0.05:0.05, and the mixture is thoroughly stirred and mixed to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and then dried, cold pressed, and cut to obtain the positive electrode sheet.

[0136] 2. Preparation of negative electrode sheet:

[0137] The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene-butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC-Na) are dissolved in deionized water in a mass ratio of 90%:5%:4%:1%, and the mixture is thoroughly stirred and mixed to prepare a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and then dried, cold pressed, and cut to obtain a negative electrode sheet.

[0138] 3. Preparation of isolation membrane:

[0139] The particle size D v Elemental silicon particles with a size of 1 μm, polyvinylidene fluoride (PVDF, weight-average molecular weight of 500,000) and dispersant polyvinyl alcohol are mixed in N-methylpyrrolidone in a mass ratio of 0.985:0.01:0.005 to obtain a mixed slurry with a solid mass content of 50%; the mixed slurry is scraped on the surface of a first substrate layer (PP material, average pore size of 50 nm) with a thickness of 7 μm to obtain a mixed material layer arranged on the first substrate layer, and while the mixed slurry is not dry, the surface of the mixed material layer away from the first substrate layer is compounded with a second substrate layer (PP material, average pore size of 50 nm) with a thickness of 7 μm by a pressing roller method, and an isolation membrane is obtained after drying; wherein, the thickness of the mixed material layer is 3 μm.

[0140] 4. Preparation of electrolyte:

[0141] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and then LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte solution. The concentration of LiPF6 in the electrolyte solution was 1 mol / L.

[0142] 5. Preparation of secondary batteries:

[0143] The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the above-prepared electrolyte is added. After packaging, standing, formation, aging and other processes, a secondary battery is obtained.

[0144] 6. Preparation of button batteries:

[0145] Lithium sheets with a diameter of 18 mm and a thickness of 500 μm were used as the positive and negative electrodes. The intermediate layer between the positive and negative electrodes was the above-mentioned isolation membrane. Electrolyte was added dropwise to assemble into a 2430 model button battery. The electrolyte was EC / DMC containing 1 mol / L LiPF6 (the volume ratio of EC and DMC was 1:1).

[0146] Examples 2-34 and Comparative Examples 1-5 are similar to Example 1, and the different parameters are detailed in Table 1.

[0147]

[0148]

[0149]

[0150] Material and battery performance testing

[0151] (1) Determination of electronic conductivity of isolation membrane:

[0152] Determination method: The positive electrode uses lithium iron phosphate (surface density 0.025g / cm 2 , the thickness of the aluminum foil is 60μm), and the negative electrode uses a graphite electrode (surface density is 0.012g / cm 2 , the thickness of the copper foil is 8μm), the middle interlayer is the isolation membrane to be tested, and the impedance test is performed using a hot pressure resistance meter with a voltage of 200V and a pressure of 600kgf to measure the resistance value of the isolation membrane; the electronic conductivity σ of the isolation membrane is calculated according to the following formula;

[0153] R=S / (σ×l)

[0154] Where R is the resistance of the isolation membrane; S is the test area of ​​the isolation membrane, that is, the area of ​​a circle with a diameter of Φ14 mm; l = H × (1-porosity), l is the thickness of the isolation membrane after the pores are eliminated under a pressure of 600 kgf, and H is the initial thickness of the isolation membrane;

[0155] The test method for the above porosity:

[0156] The thickness of the diaphragm is measured with a caliper, the length and width of the diaphragm are measured with a ruler and the area of ​​the diaphragm is calculated, and then the apparent volume V of the diaphragm is calculated. The weight M of the diaphragm is tested with a balance with a precision of 10,000, ρ represents the theoretical density of the substrate, and the porosity P of the diaphragm is calculated according to the following formula.

[0157]

[0158] (2) Particle size D v Determination of 50:

[0159] Determination method: Add a certain amount of deionized water to the sample, ultrasonicate it for 10 minutes, and after the sample is completely dispersed, use a laser particle size analyzer to measure the particle size D of the sample. v 50.

[0160] (3) Determination of thickness:

[0161] Determination method: After the sample is flattened, use a micrometer to measure the thickness at more than ten different locations, and take the average value to obtain the thickness of the sample.

[0162] (4) Determination of average pore size:

[0163] Determination method: Using the mercury intrusion method, a certain amount of sample is placed in the mercury intrusion instrument and the average pore size is obtained by testing.

[0164] (5) Electrolyte absorption test of isolation membrane:

[0165] Experimental Method: Bake the separator at 100°C for at least 6 hours to ensure thorough drying. Cut the dried separator into samples of a fixed size and measure their thickness (d). Mount the sample on a sample stage and, using a capillary with a flush end, draw electrolyte (density ρ) to a specified height h. Turn on the microscope and adjust the lens magnification to clearly see the capillary and sample. Bring the capillary end into contact with the sample. Use a stopwatch to time the drop of the liquid level. When the liquid level has completely dropped, read the aspiration time t and record the data. Calculate the average aspiration rate v of the separator using the formula.

[0166] v = π × (d / 2) 2 ×h×ρ / t

[0167] (6) Thermal shrinkage test of isolation film:

[0168] Experimental method: Lay out the isolation film and cut it into samples of 100mm×100mm size. Set the oven to 120℃, keep it warm for 1 hour, then put the sample in. Continue to keep it warm for 4 hours, then take out the sample, cool it, test the size of the sample, calculate the heat shrinkage ratio in two directions respectively, and then take the average value of the two directions.

[0169] (7) Determination of short-circuit time:

[0170] The button battery was charged and discharged using a Xinwei charge and discharge tester. First, it was left to stand for 10 minutes and the current density was 4 mA / cm 2 Charge for 1 hour, let it stand for 10 minutes, and then charge it at a current density of 4 mA / cm 2Discharge for 1 hour, then repeat the above operation for multiple cycles. The maximum voltage minus the minimum voltage during the first charge and discharge process is taken as the normal voltage distribution. If the voltage distribution in the subsequent charge and discharge cycles (maximum voltage minus minimum voltage in the same cycle) is less than 0.3 times the normal voltage distribution, the separator is determined to be in a short-circuit state, the cycle is stopped, and the operating time at this time is recorded as the short-circuit time.

[0171] The above results are shown in Table 2.

[0172] Table 2: Performance test results of Examples 1-34 and Comparative Examples 1-5

[0173]

[0174]

[0175] According to the above results, it can be seen that: compared with comparative examples 1-5, the isolation membrane of the present application delays the occurrence time of lithium dendrites piercing the diaphragm, delays the occurrence of short circuit in the secondary battery, and extends the service life of the battery; compared with comparative examples 1-3, the present application improves the wettability of the isolation membrane to the electrolyte, increases the transmission rate of lithium ions, increases the battery charge and discharge rate, and the isolation membrane has better thermal shrinkage performance, which improves the safety of the secondary battery.

[0176] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A separator comprising a first substrate layer, a mixed material layer, and a second substrate layer; the mixed material layer is disposed between the first substrate layer and the second substrate layer; the mixed material layer comprises an inorganic material and a dispersant; wherein: The electronic conductivity σ of the isolation film satisfies: 1×10 -13 mS / cm<σ<1×10 -1 mS / cm.

2. The isolation film according to claim 1, wherein The inorganic material is selected from one or more of the following (1)-(3): (1) Elemental silicon; (2) oxides, nitrides and fluorides of one or more elements selected from silicon, aluminum, iron, titanium, cobalt, nickel, manganese, tin, zinc, barium and copper; (3) Phosphates of one or more elements selected from aluminum, iron, titanium, cobalt, nickel, manganese, tin, zinc, barium and copper.

3. The separator according to claim 1 or 2, wherein: The inorganic material is one or more selected from silicon dioxide, silicon monoxide, silicon, zinc oxide, tin oxide, copper oxide, iron phosphate, barium titanate, cobalt oxide, manganese oxide, iron oxide, copper nitride and lithium aluminum titanium phosphate.

4. The separator according to any one of claims 1 to 3, wherein Based on the total mass of the mixed material layer, the mass content of the inorganic material is 75%-99.7%, and the mass content of the dispersant is 0.1%-15%, optionally 0.1%-5%.

5. The separator according to any one of claims 1 to 4, wherein The particle size D of the inorganic material v The ratio of the average pore size of 50 to the average pore size of the first substrate layer is 1:1-243:1; and / or, The particle size D of the inorganic material v The ratio of 50 to the average pore size of the second substrate layer is 1:1-243:

1.

6. The isolation membrane according to any one of claims 1 to 5, wherein the dispersant is selected from one or more of sodium polyacrylate, ammonium polyacrylate, sodium hexafluorophosphate, sodium carboxymethyl cellulose, hydrolyzed polymaleic anhydride, acrylic acid block polymer, polyester block polymer, polyethylene glycol-type polyol, polyvinyl alcohol and polyethyleneimine derivatives.

7. The separator according to any one of claims 1 to 6, wherein The thickness of the mixed material layer is 0.5-10 μm; Optionally, the isolation film has a thickness of 11-24 μm.

8. The separator according to any one of claims 1 to 7, wherein The mixed material layer further comprises a polymer, wherein the polymer is selected from one or more of styrene-butadiene rubber, water-based acrylic resin, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, polyacrylic acid, carboxymethyl cellulose, polyvinyl alcohol and polyvinyl butyral; Optionally, based on the total mass of the mixed material layer, the mass content of the polymer is 0.1%-20%.

9. The separator according to any one of claims 1 to 8, wherein A protective layer is further provided on the surface of the first substrate layer away from the mixed material layer and / or on the surface of the second substrate layer away from the mixed material layer; optionally, the protective layer comprises one or more selected from aluminum oxide and boehmite.

10. A method for preparing an isolation membrane, comprising the following steps: coating a slurry comprising an inorganic material, a dispersant, and optionally a polymer on the first substrate layer to obtain the first substrate layer provided with the mixed material layer; Laminating a second substrate layer on the surface of the mixed material layer away from the first substrate layer to obtain a separator; The isolation film includes the first substrate layer, the mixed material layer and the second substrate layer; the mixed material layer is arranged between the first substrate layer and the second substrate layer; the mixed material layer contains the inorganic material, the dispersant and the optional polymer; the electronic conductivity σ of the isolation film satisfies: 1×10 -13 mS / cm<σ<1×10 -1 mS / cm; in, The inorganic material and dispersant are as described in any one of claims 1 to 9 , and the polymer is as described in claim 8 . 11 . A secondary battery comprising the separator according to claim 1 or the separator produced by the method according to claim 10 .

12. The secondary battery according to claim 11, wherein The positive electrode active material includes one or more selected from lithium iron phosphate, nickel-cobalt-manganese ternary material, lithium manganate, lithium cobaltate and lithium nickelate; and / or, The negative electrode active material includes one or more selected from graphite, silicon-carbon compounds, silicon-oxygen compounds and lithium metal.

13. An electrical device comprising the secondary battery according to claim 11 or 12.

Citation Information

Cited By

  • Winding type electrode assembly and preparation method thereof, battery monomer, battery and power utilization device

    CN120933499A